2020
DOI: 10.1016/j.bja.2019.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative xenon for prevention of delirium after on-pump cardiac surgery: a randomised, observer-blind, controlled clinical trial

Abstract: Initial results of the current study were presented as a chapter of the PhD thesis of L. Al tmimi, November 12, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…In our study, Dexm reduced POD after all types of anesthesia and after general anesthesia compared with the control group. These results are in close agreement with a previous report by Al Tmimi et al [ 13 ] and Shen et al [ 14 ] in which the risks of POD were decreased in elderly patients after non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, Dexm reduced POD after all types of anesthesia and after general anesthesia compared with the control group. These results are in close agreement with a previous report by Al Tmimi et al [ 13 ] and Shen et al [ 14 ] in which the risks of POD were decreased in elderly patients after non-cardiac surgery.…”
Section: Discussionsupporting
confidence: 94%
“…Of these, 182 studies were discarded after reviewing the title and abstracts for the following reasons: related to other topics, designed as systematic reviews, reviews or retrospective studies, and conference abstracts. The full texts of the 63 remaining studies were reviewed in detail; 12 studies were excluded for the following reasons: three were study protocols [ 25 27 ], two were editorials [ 13 , 28 ], four were systematic reviews, [ 9 12 ] and three did not report the outcome of our interest (two compared an inhalational agent [ 13 , 29 ] and one was compared in the PCA regimen [ 30 ]). Thus, 51 studies with a total of 22,565 patients that included 18 different pharmacological interventions were included in this NMA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the study involved a small sample size therefore generalization of these findings will not be appropriate unless backed by adequately powered randomized studies. Later Al Tmimi et al 26 conducted a randomized, observer-blind, controlled trial in which 190 patients involving 65 years or older patients underwent on-pump cardiac surgery. Patients were randomized to receive xenon or sevoflurane as anesthetic.…”
Section: Enon and P Ostoperative C Ognitive D Ysfunction In C mentioning
confidence: 99%
“…On analysis authors concluded that xenon anesthesia did not result in a significant reduction in POCD and therefore did not recommend xenon for preventing POCD. 26 Stoppe et al 27 randomized 30 patients undergoing coronary artery bypass grafting under CPB to receive either xenon anesthesia or sevoflurane anaesthesia. They compared systemic and pulmonary dynamics in both groups and also parameters like blood loss, inotropic support, regional cerebral tissue oxygenation, and postoperative delirium in both groups using CAM-ICU.…”
Section: Enon and P Ostoperative C Ognitive D Ysfunction In C mentioning
confidence: 99%
“… 30 A pilot study in off-pump cardiac surgery suggested that xenon anesthesia reduced the incidence of POD compared to conventional inhalational anesthesia 31 ; however a larger study from the same group investigating on-pump cardiac surgery showed no difference in POD incidence for xenon anesthesia when compared to the inhalational anesthesia group. 32 …”
Section: Introductionmentioning
confidence: 99%